HEGEMONI RELIGIO-PATRIARKAT ATAS PEREMPUAN DALAM DINAMIKA SOSIO-KULTURAL MASYARAKAT MADURA - umam shohebul (PSGA LP2M IAIN Pontianak, 2021)
This study aims to analyze the religio-patriarchal hegemony of the Madurese community towards women. How does gender discrimination in Madura urge women not to have authority over their own bodies, due to the strict patriarchal culture and religious attitudes of people who tend to be fanatical and conservative. The area chosen as the locus of this study was Madura Island, covering Sampang Regency in West Tobaih Village, Pamekasan Regency in Torjun Village, Sumenep Regency in Bragung Village. The reason for the selection of the three regions is because the orthodox religious attitude of the people is still very thick, and is the main buffer of patriarchal culture. The method used in this study is qualitative anthropological through interviews with informants, as well as observations in the field. This study succeeded in identifying, gender inequality experienced by women in Madura, in addition to the strengthening of patriarchal culture and religious attitudes that are conservative and orthodox, women themselves become a driving force that reinforces gender discrimination against women in Madura, where the distribution of religious knowledge is gender biased , distributed by women to other women in the community. Another finding in this study is that pesantren are the main center for the development of interpretation of classical Islamic literature into gender bias. Therefore, a review of texts and learning strategies, especially in pesantren, is needed to make women more empowered, and not pressure women to become second class after men, so that the vulnerability of women in the family or the public sphere is not strengthened .